PO 18079 - Arthroscopic medial and lateral ligament repair for multidirectional ankle instability - Barbachan Mansur, Nacime Salomão; Cavalcante Lemos, André Vitor Kerber; Furtado Fonseca, Lucas; Baumfeld, Tiago Soares; Baumfeld, Daniel Soares; de Souza Nery, Caio Augusto (Scientific Journal of the Foot & Ankle, 2019)
Introduction: The extremely high prevalence of sprains in the population has led to a large number of patients with lateral ankle instability. The persistence of this condition can lead to progressive loosening of the medial containment structures, generating multidirectional rotational instability. Treatment of the deltoid complex through ligamentoplasty of its components has been proposed as a solution for these patients, and the arthroscopic technique is a currently described alternative. Methods: This is a retrospective study of 10 patients (11 ankles) diagnosed with multidirectional instability who underwent ankle arthroscopy with medial and lateral ligament reconstruction (arthroscopic Brostrom technique) from January 2017 to January 2019. All patients filled out an epidemiological questionnaire and were assessed for ankle pain and function using the Pain Visual Analog Scale (VAS) and the American Orthopedic Foot and Ankle Society (AOFAS) scale at the last follow-up evaluation, at a mean of 12 months (6-24 months). Results: All patients showed signs of associated medial instability during the arthroscopy. Four ankles had associated osteochondral injuries. One ankle also had associated syndesmotic instability. The mean AOFAS score was 82.6 at the last follow-up evaluation, and the mean VAS score was 2.1. No patient had complications related to surgery or loss of ankle mobility greater than 5 degrees (ankle or subtalar joint). Eight patients described the outcome as excellent, and 2 described it as good. All patients returned to sports after 6 months of follow-up. No complaints of instability or positive ligament tests were observed. Conclusion: Combined medial and lateral arthroscopic ankle ligamentoplasty is an effective and safe alternative for the treatment of multidirectional instability refractory to conservative treatment. The inclusion of the deltoid complex and the reduced invasiveness of this technique may improve the clinical outcomes of these patients.